PERANAN “AHLI K3” DALAM MENDORONG EFEKTIFITAS PENGAWASAN K3 SANGAT PENTING DAN STRATEGIS - Generousdi Generousdi; Darman Dapersal Dinar (Jurnal Teknik Mesin, 2004)
Management of human reassures may function to keep safety and healthy working rules based an all aspects and all places. It can be applied for both business purpose likeworking in workshop, office, laboratory and other and for domestic purposes. Accident can be avoided by establishing required rules, standardization, supervision, research and other useful activities that focus on techniques, medical, psychological, statistic, education, motivation and insurance as well as efficiency regulation.